Penanganan Hoaks Keagamaan di Sosial Media Melalui Literasi Digital Milenial - Munabiah Lestari, Munabiah; Saidah, Musfiah (Meyarsa: Jurnal Ilmu Komunikasi dan Dakwah, 2023)
The millennial generation, as the largest contributor to the composition of the population in the demographic bonus. Identical to the productive and energetic young generation, the millennial generation is often labeled as an Agent of Change. Currently the world, especially Indonesia, is facing an era of openness in social media. One of the most worrying problems in the era of openness is the existence of religious hoaxes that divide religious communities. A pluralistic country like Indonesia, can be said to be in great threat if religious hoaxes continue to run rampant. This study aims to determine the condition of religious hoaxes and literacy in Indonesia. Furthermore, the extent to which religious hoaxes can be overcome with digital literacy will be something interesting in this research. The method used in this research is a survey on the condition of religious hoaxes in Indonesia. The results of the study found that the distance between religious hoax information and social media users was very close. Religious hoax information on social media, including radical sites, terrorism cases, and hate speech. Many Indonesian people do not have the ability to check data. So that the presence of the "Millennial Digital Literacy" solution can be used as a solution for handling religious hoaxes in Indonesia.